Investigating the effective factors influencing surface runoff generation in urbacatchments a review - Rezaei A.R.; Ismail Z.B.; Niksokhan M.H.; Ramli A.H.; Sidek L.M.; Dayarian M.A. (Desalination Publications, 2023)
catchment; climate change; hydrological modeling; literature review; runoff; stormwater; urbanization